Lifelong Learning as generative leverage for a new learnfare - Costa, Massimiliano (Formazione & insegnamento, 2016)
The life-long, life-wide, and life-deep framework provides a broad conceptual framework for assessing how, where and why people in learnfare society learns. This paper aims to contribute to an understanding of how learnfare, based on strengthening the agency of citizens, gives the capability to freely choose and realize their human and social life projects. In the transition to learnfare, the right to learn throughout life it is no longer tied to labor market needs but the social development of innovation. This new approach emphasizes a newfound centrality of the person who becomes responsible of the learning process in an autonomously and self-directed way.